Plant extracts for controlling the post-harvest anthracnose of banana fruit - M.E.S. Cruz; K.R.F. Schwan-Estrada; E. Clemente; A.T. Itako; J.R. Stangarlin; M.J.S. Cruz (Universidade Estadual Paulista, 2013)
In banana, fruit rot is incited by Colletotrichum musae which has been the most serious post-harvest disease of immature and mature fruit. The usual control by fungicides prohibited in many countries reduces their commercial value. Therefore, two experiments were conducted to evaluate the antimicrobial activity of alternative products to the synthetic fungicides. First, berries naturally infected by anthracnose were immersed into Azadirachta indica and citric extracts at 2 and 4% (v/v) for 3 minutes and stored for 11 days under environmental conditions. Next, other berries were immersed into essential oil emulsions of Allium sativum, Copaifera langsdorfii, Cinnamomum zeylanicum and Eugenia caryophyllata at 5% for 3 minutes but stored for 11 days. Berries immersed into distilled water were used as control-treatments. The percentage of disease incidence observed in the control-treatment was similar to the ones observed in the extract of A. indica at 2%. The control-treatment showed disease severity of 75.13% and the percentage of disease control was 20.85%. Fruit immersed into distilled water presented less effectiveness than the ones immersed into citric extracts, which promoted the highest effectiveness. Citric extract at 4% was the most efficient treatment because the disease incidence was 19.44%, the disease severity was 9.34% and the disease control was 90.16%. Less severity and, consequently, more disease control were achieved by immersing the berries into the emulsion of essential oil of A. sativum, followed by treatments with C. langsdorfii, E. caryophyllata and C. zeylanicum.